Beatrice Prior’s Masculinity Appearance and Feminism in Veronica Roth’s Divergent. - Afina Unzila Tiarasari (LITERA KULTURA : Journal of Literary and Cultural Studies, 2021)
Abstract The masculine appearance will be discussed in this study. The main character of the Divergent novel written by Veronica Roth, Beatrice Prior, will be the object of this study. The method of this study were to first reading and analyzed the issues. The first problem discussed is how the main character shows her masculine appearance in this novel and the second problem concern the reflection of feminism of the main character, Beatrice Prior. Based on the analysis, this study has been answering the problem of this study. There are two different answers with a different question which has been showing in this study. The first one is Beatrice Prior has more masculine character than feminine in the form of Courageous and Heroism. And second, the last one is not only the masculine appearance that Beatrice Prior has but also the feminism reflection that she has been express in the novel. Keywords: masculinity appearance, women power, feminism reflection. Abstrak Penampilan maskulinitas dan refleksi feminisme akan dibahas dalam penelitian ini. Tokoh utama novel Divergent karya Veronica Roth, Beatrice Prior, akan menjadi objek penelitian ini. Metode yang digunakan dalam studi ini adalah metode first reading dan menganalisis masalah. Masalah pertama yang dibahas adalah bagaimana tokoh utama menunjukkan penampilan maskulinitasnya dalam novel ini dan masalah kedua menyangkut refleksi feminisme tokoh utama, Beatrice Prior. Berdasarkan analisis tersebut maka penelitian ini telah menjawab permasalahan penelitian ini. Ada dua jawaban berbeda dengan pertanyaan berbeda yang ditampilkan dalam penelitian ini. Pertama, Beatrice Prior memiliki karakter yang lebih maskulin daripada feminin dalam bentuk keberanian dan kepahlawanan. Dan yang kedua bukan hanya penampilan maskulinitas yang dimiliki Beatrice Prior, tetapi juga refleksi feminisme yang diungkapkannya dalam novel. Kata Kunci: penampilan maskulinitas, kekuatan wanita, refleksi feminisme.